2002
DOI: 10.1161/01.cir.0000013773.67850.ba
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Myocardial Acceleration During Isovolumic Contraction as a Novel Noninvasive Index of Right Ventricular Contractility

Abstract: Background-We have demonstrated that myocardial acceleration during isovolumic contraction (IVA) is a sensitive index of left ventricular contractile function. In this study, we assessed the utility of IVA to measure right ventricular (RV) contractile function. Methods and Results-We examined 8 pigs by using tissue Doppler imaging of the RV free wall and simultaneous measurements of intraventricular pressure, volume, maximal elastance (e max ), preload recruitable stroke work, and dP/dt max by conductance cath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
377
4
8

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 422 publications
(401 citation statements)
references
References 36 publications
11
377
4
8
Order By: Relevance
“…[2][3][4] We have recently shown that myocardial acceleration during isovolumic contraction (IVA) derived from TDE is a robust measurement of right ventricular contractile function. 5 In our experiments, we found that IVA was sensitive to small changes in inotropy but unaffected by large changes in right ventricular preload and afterload. 5 We hypothesized that, in a similar way, myocardial acceleration during isovolumic contraction (IVA) may reflect LV myocardial contractile function.…”
supporting
confidence: 51%
See 2 more Smart Citations
“…[2][3][4] We have recently shown that myocardial acceleration during isovolumic contraction (IVA) derived from TDE is a robust measurement of right ventricular contractile function. 5 In our experiments, we found that IVA was sensitive to small changes in inotropy but unaffected by large changes in right ventricular preload and afterload. 5 We hypothesized that, in a similar way, myocardial acceleration during isovolumic contraction (IVA) may reflect LV myocardial contractile function.…”
supporting
confidence: 51%
“…5 In our experiments, we found that IVA was sensitive to small changes in inotropy but unaffected by large changes in right ventricular preload and afterload. 5 We hypothesized that, in a similar way, myocardial acceleration during isovolumic contraction (IVA) may reflect LV myocardial contractile function. Furthermore, although we were able to show that myocardial acceleration could describe the force-frequency relationship in the right ventricle, no noninvasive index has been used previously in the LV in either an experimental or clinical setting.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…The S' velocity has been shown to be load and inotropic dependent in an animal model. 22 In humans, S' velocity has been found to be stable under load alterations in Table 1 Demographics Group E (n = 24) Group V (n = 26) All (n = 50) Age (yr)…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial acceleration during isovolumic contraction is another measure of load-independent RV function in healthy animals, but validation in PAH is required. 47 In patients with PAH, a reduced longitudinal strain has been demonstrated, with the most severe impairments in patients with RV failure. [48][49][50][51][52][53][54] Regional heterogeneity was an important feature of a dysfunctional RV in which the apical region is the most affected.…”
Section: Regional Rv Function and Strainmentioning
confidence: 99%